Optimizing Management to Reduce the Mortality of COVID-19: Experience From a Designated Hospital for Severely and Critically Ill Patients in China - Zhu, Wei; Zhang, Huaqiu; Li, Yong; Ding, Zeyang; Liu, Zhuo; Ruan, Yajun; Feng, Huan; Li, Ganxun; Liu, Bo; He, Fan; Zhou, Ning; Jiang, Jiangang; et al. (Frontiers in Medicine, 2021)
Background: The coronavirus disease 2019 (COVID-19) has swept through the world at a tremendous speed, and there is still limited data available on the treatment for COVID-19. The mortality of severely and critically ill COVID-19 patients in the Optical Valley Branch of Tongji Hospital was low. We aimed to analyze the available treatment strategies to reduce mortality. Methods: In this retrospective, single-center study, we included 1,106 COVID-19 patients admitted to the Optical Valley Branch of Tongji Hospital from February 9 to March 9, 2020. Cases were analyzed for demographic and clinical features, laboratory data, and treatment methods. Outcomes were followed up until March 29, 2020. Results: Inflammation-related indices (hs-CRP, ESR, serum ferritin, and procalcitonin) were significantly higher in severe and critically ill patients than those in moderate patients. The levels of cytokines, including IL-6, IL2R, IL-8, and TNF-α, were also higher in the critical patients. Incidence of acute respiratory distress syndrome (ARDS) in the severely and critically ill group was 23.0% (99/431). Sixty-one patients underwent invasive mechanical ventilation. The correlation between SpO2/FiO2 and PaO2/FiO2 was confirmed, and the cut-off value of SpO2/FiO2 related to survival was 134.43. The mortality of patients with low SpO2/FiO2 (<134.43) at intubation was higher than that of patients with high SpO2/FiO2 (>134.43) (72.7 vs. 33.3%). Among critical patients, the application rates of glucocorticoid therapy, continuous renal replacement therapy (CRRT), and anticoagulation treatment reached 55.2% (238/431), 7.2% (31/431), and 37.1% (160/431), respectively. Among the intubated patients, the application rates of glucocorticoid therapy, CRRT, and anticoagulation treatment were respectively 77.0% (47/61), 54.1% (33/61), and 98.4% (60/61). Conclusion: No vaccines or specific antiviral drugs for COVID-19 have been shown to be sufficiently safe and effective to date. Comprehensive treatment including ventilatory support, multiple organ function preservation, glucocorticoid use, renal replacement therapy, anticoagulation, and restrictive fluid management was the main treatment strategy. Early recognition and intervention, multidisciplinary collaboration, multi-organ function support, and personalized treatment might be the key for reducing mortality.